E-Service Quality in the Gojek Application for Customer Satisfaction - Amanda Putri Prasetya; Laura Theodora Loviga; Mohamad Zein Saleh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Technological developments that impact digital transformation in various sectors of the Company. E-Service provision has become an important aspect that affects customer satisfaction in various industries in today's digital era. This study aims to determine how E-Service Quality in the gojek application for customer satisfaction with the results stating that E-Service Quality in the gojek application has various aspects that can increase customer satisfaction such as (tangible, reliability, responsiveness, assurance, and empathy) so that increasing these aspects will cause a sense of satisfaction, pleasure or happiness for consumers. By understanding and optimizing E-Service Quality in gojek applications can increase customer satisfaction and maintain a competitive advantage in today's digital era.